Binder for lithium secondary battery and electrode for lithium secondary battery using same
By using modified polytetrafluoroethylene composite particles coated with modified polyacrylic polymer as the binder, the problems of uneven dispersion and insufficient adhesion in the manufacture of thick film electrodes are solved, and the uniform distribution of electrode materials and high mechanical strength are achieved, and the electrical performance of the battery is improved.
Patent Information
- Application Number
- JP2024536411
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-09-15
- Filing Date
- 2023-08-21
- Publication Date
- 2025-02-04
- Estimated Expiration
- 2043-08-21
AI Technical Summary
In the prior art, when the traditional polytetrafluoroethylene-based adhesive is produced, it is prone to fibrosis due to shear force, resulting in uneven dispersion of electrode materials, affecting the durability of the electrode and battery performance, and it is difficult to maintain the adhesion and conductivity of the thick film electrode during the dry manufacturing process.
The polytetrafluoroethylene composite particles coated with modified polyacrylic polymer are used as the binder to form a core-shell structure, which improves the dispersion and adhesion of the polytetrafluoroethylene and enhances the durability and conductivity of the electrode.
The modified polymer-coated polytetrafluoroethylene composite particles can effectively prevent the aggregation of polytetrafluoroethylene particles, improve the thickness uniformity and mechanical strength of the electrode, and improve the capacity retention rate and electrical performance of the battery.
Smart Images

Figure 2025503460000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a binder for lithium secondary batteries and an electrode for lithium secondary batteries using the same. More specifically, the present invention relates to a binder for lithium secondary batteries containing polytetrafluoroethylene modified with an acrylic polymer and an electrode for lithium secondary batteries using the same.
[0002] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0116479 dated September 15, 2022, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference. [Background technology]
[0003] With technological development and increasing demand for mobile devices, the demand for secondary batteries as an energy source is rapidly increasing. Among such secondary batteries, lithium secondary batteries, which have high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used.
[0004] When manufacturing an electrode for a lithium secondary battery, an electrode active material, a conductive material, and a binder are mixed to prepare a mixture containing the electrode active material. The mixture thus prepared is applied onto an electrode current collector, and then pressed by equipment such as a roll to manufacture an electrode. When the roll is pressed, a shear force is applied to a binder such as polytetrafluoroethylene (PTFE) from the surface in contact with the roll, and the binder is fibrillated. This fibrillation occurs in the machine direction (MD) of the roll, and relatively, the majority of the binder is formed from the binder located on the surface of the electrode. Even after the binder is fibrillated, the electrode active material, conductive material, and binder located inside the electrode are still dispersed in the form of small particles, which may result in insufficient durability of the electrode. The durability of the electrode is a factor that may be related to the lifespan of the electrode and may directly affect the performance of the battery.
[0005] As users' demand for high energy density secondary batteries is rapidly increasing, research into electrodes with a large thickness (thick film electrodes) is ongoing in the technical field. In the conventional electrode manufacturing method in which a slurry containing an electrode active material is coated to manufacture an electrode using a wet method, the conductive material and binder move to the top of the coating layer during drying, which leads to problems such as a decrease in conductivity and low adhesive strength between the current collector and the electrode active material, making it difficult to maintain the quality of the manufactured electrode while increasing the electrode thickness. In the new electrode manufacturing method in which an electrode is manufactured using a dry method, the functionality of the fiberized binder must also be maximized, otherwise the adhesive strength between the particles of the electrode active material, conductive material, and binder will be insufficient, making it difficult to manufacture an electrode with a large thickness and high durability.
[0006] Therefore, the present inventors have continuously studied a method for manufacturing a thick-film electrode having high durability by improving the functionality of a binder while manufacturing an electrode by a dry method, and have completed the present invention. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Korean Patent Publication No. 2014-0136952 Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention provides a binder for a lithium secondary battery, which includes polytetrafluoroethylene modified with an acrylic polymer, and which is easy to handle and can improve the functionality of the battery when applied, and an electrode for a lithium secondary battery using the same. [Means for solving the problem]
[0009] According to a first aspect of the present invention, A binder for lithium secondary batteries is provided that includes composite particles of polytetrafluoroethylene structure coated with an acrylic polymer.
[0010] In one embodiment of the present invention, the composite particles have an average diameter of 0.01 μm to 2 μm.
[0011] In one embodiment of the present invention, the acrylic polymer is a polymer of a monomer containing an alkyl acrylate, an alkyl methacrylate, or a combination thereof, and the alkyl has 1 to 10 carbon atoms.
[0012] In one embodiment of the present invention, the acrylic polymer has a glass transition temperature of 60°C to 150°C.
[0013] In one embodiment of the present invention, the acrylic polymer has a weight average molecular weight of 10,000 g / mol to 300,000 g / mol.
[0014] In one embodiment of the present invention, the acrylic polymer contains 40% by weight to 90% by weight of methyl methacrylate based on the total weight of the monomers.
[0015] In one embodiment of the present invention, the acrylic polymer is a copolymer of monomers including methyl methacrylate and n-butyl acrylate.
[0016] In one embodiment of the present invention, the acrylic polymer is coated on the polytetrafluoroethylene in an amount of 5% by weight to 40% by weight based on the total weight of the composite particles.
[0017] In one embodiment of the present invention, the n-butyl acrylate is contained in an amount of 10 parts by weight to 60 parts by weight based on 100 parts by weight of methyl methacrylate.
[0018] In one embodiment of the present invention, the monomer further comprises acrylic acid or methacrylic acid.
[0019] In one embodiment of the present invention, the acrylic acid or methacrylic acid is contained in an amount of 0.1% by weight to 40% by weight based on the total weight of the monomers.
[0020] In one embodiment of the present invention, the polytetrafluoroethylene has a standard specific gravity (SSG) of 2.3 or less.
[0021] According to a second aspect of the present invention, The binder, the electrode active material, and the conductive material are mixed together and then pressed to provide an electrode for a lithium secondary battery.
[0022] In one embodiment of the present invention, the binder is contained in the electrode in an amount of 0.1% by weight to 10% by weight based on the total weight of the binder, the electrode active material, and the conductive material. Effect of the Invention
[0023] The binder for lithium secondary batteries according to one embodiment of the present invention can solve problems such as aggregation that may occur when handling conventional binders by modifying polytetrafluoroethylene into an acrylic polymer.
[0024] In addition, an electrode manufactured using the binder has excellent physical properties such as low thickness deviation and high tensile strength, and when the electrode is applied to a battery, the battery performance such as capacity retention rate can be improved. [Brief description of the drawings]
[0025] [Figure 1] 1 is a TEM and TEM-EDX Mapping image showing a composite particle binder having a polytetrafluoroethylene structure coated with an acrylic polymer according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] The embodiments provided in accordance with the present invention can all be achieved by the following description. It should be understood that the following description describes preferred embodiments of the present invention, and that the present invention is not necessarily limited thereto.
[0027] Unless the measurement conditions and methods are specifically described for the physical properties described in this specification, the physical properties are measured according to the measurement conditions and methods commonly used by those of ordinary skill in the art.
[0028] The present invention provides a binder for lithium secondary batteries, comprising polytetrafluoroethylene modified with an acrylic polymer. Polytetrafluoroethylene, which is generally used as a binder in the dry process of electrodes in the art, is a long-chain polymer that maintains a stable phase at or below the phase transition temperature of 19°C. However, at room temperatures above 19°C, twisted spiral chains are easily unraveled and fiberization easily proceeds, and it has the property of aggregation even when a fine shear force is applied. In particular, at room temperatures around 25°C, which exceeds the phase transition temperature of 19°C, it is easy to form fine fibers and aggregate even under powder transportation and stirring conditions where shear force may be frequently applied, so that it is not easy to uniformly disperse the powder during the dry process of electrode production. Therefore, the polytetrafluoroethylene requires expensive maintenance costs for refrigerated transportation and storage when handled, and special attention is also required for the operating temperature. In order to solve such problems of polytetrafluoroethylene, the present invention modifies polytetrafluoroethylene with an acrylic polymer.
[0029] There are various methods for modifying the polytetrafluoroethylene with an acrylic polymer, but in one embodiment of the present invention, the outside of a polytetrafluoroethylene particle is coated with an acrylic polymer to provide a composite particle of an acrylic polymer / polytetrafluoroethylene structure. The composite particle may be expressed as a core-shell structure, in which the core is made of polytetrafluoroethylene and the shell is made of an acrylic polymer.
[0030] According to one embodiment of the present invention, when polytetrafluoroethylene particles are coated with an acrylic polymer, the problem of polytetrafluoroethylene aggregation can be solved, so that the polytetrafluoroethylene contained therein can be a polymeric material with a high degree of fiberization. According to one embodiment of the present invention, the polytetrafluoroethylene has a standard specific gravity (SSG) of 2.3 or less. The standard specific gravity is a specific gravity defined by a measurement method according to Japanese Industrial Standards (JIS) K6892. Since the standard specific gravity shows a negative correlation with the average molecular weight, a low standard specific gravity of the polytetrafluoroethylene means a high molecular weight. Considering that the higher the molecular weight, the better the degree of fiberization, the lower limit of the standard specific gravity range may not be so important, but may be, for example, 2.0 or more. In the composite particles according to one embodiment of the present invention, the standard specific gravity can be minimized because polytetrafluoroethylene is easier to handle.
[0031] FIG. 1 provides TEM (Transmission Electron Microscope) and TEM-EDX (Energy Dispersive X-ray Spectroscopy) mapping images showing a composite particle binder of polytetrafluoroethylene structure coated with an acrylic polymer according to one embodiment of the present invention. As can be seen in FIG. 1, in the polytetrafluoroethylene coated with an acrylic polymer, the polytetrafluoroethylene particles do not aggregate with each other due to the acrylic polymer located on the outside, and the core-shell type composite particles can be easily separated while maintaining their original shape. Such composite particles have high dispersibility when mixed with the electrode active material and conductive material in the electrode active material layer, and can increase the binder application efficiency by forming fibers even at a small content.
[0032] According to one embodiment of the present invention, the composite particles have an average diameter of 0.01 μm to 2 μm. The average diameter is calculated by measuring the particle sizes of each particle distinguished in a TEM analysis image and then calculating the arithmetic average value of the measured values. Specifically, the average diameter of the composite particles may be 0.01 μm to 2 μm, 0.01 μm to 1.5 μm, or 0.01 μm to 1 μm. Such an average diameter of the composite particles helps polytetrafluoroethylene to be fiberized at an appropriate level while increasing the dispersibility of the composite particles in the electrode active material layer.
[0033] Since the polytetrafluoroethylene can easily aggregate at room temperature, the polytetrafluoroethylene may also aggregate during the preparation of the composite particles, making it difficult to control the particle size. Therefore, for the convenience of operation, the composite particles are prepared by adding a dispersant to uniformly disperse the polytetrafluoroethylene, and then coating the acrylic polymer. Due to the characteristics of the preparation method, a small amount of dispersant may be detected between the polytetrafluoroethylene and the acrylic polymer. The core polytetrafluoroethylene and the shell acrylic polymer do not necessarily need to be strongly bonded to each other, and even if the adhesive strength between the core and shell is not high due to the presence of the dispersant, the core component can be more easily released when the shell is melted / destroyed, which is an advantage. The dispersant is not particularly limited as long as it is a material that does not easily undergo a side reaction with the polytetrafluoroethylene and the acrylic polymer and is commonly used in the art. For example, the dispersant may be an ethylene glycol-based nonionic surfactant, and in particular, Tween 20, Tween 60, Tween 80, Brij L23, Brij 020, triton x-100, or tergitol 100X may be used.
[0034] The acrylic polymer in the composite particles is not particularly limited in type as long as it can form a coating layer and prevent the aggregation of polytetrafluoroethylene. According to one embodiment of the present invention, the acrylic polymer is a polymer of a monomer including alkyl acrylate, alkyl methacrylate, or a combination thereof. In the acrylic polymer, the polymerization units of alkyl acrylate and alkyl methacrylate may be 20 mol% or more, 50 mol% or more, or 70 mol% or more. Here, the alkyl may be adjusted to an appropriate level in consideration of the physical properties of the coating layer, and in one embodiment of the present invention, an alkyl having 1 to 10 carbon atoms is used. The alkyl may be a linear or branched substituent, and may be substituted or unsubstituted alkyl. The functional group substituted on the alkyl is not particularly limited as long as it is commonly used in the art, and is preferably one that is not highly reactive with other components of the electrode active material layer, and for example, an alkyl functional group such as methyl or ethyl, a halogen functional group such as fluorine, a hydroxide functional group, an alkoxy functional group such as methoxy or ethoxy, an epoxy functional group, etc. may be used.
[0035] According to one embodiment of the present invention, the acrylate monomer forming the acrylic polymer is selected from the group consisting of methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, cyclohexyl acrylate, glycidyl acrylate, and combinations thereof, and the methacrylate monomer forming the acrylic polymer is selected from the group consisting of methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, cyclohexyl methacrylate, glycidyl methacrylate, and combinations thereof, and the acrylate monomer and the methacrylate monomer may be used in combination.
[0036] The acrylic polymer may be composed of one or more monomers, and if the monomer is two or more alkyl acrylates or alkyl methacrylates, it may be a copolymer. Therefore, in this specification, the term "polymer" may be interpreted as including a copolymer. The acrylic polymer is formed by linking monomers while breaking double bonds present in the acrylic monomers into single bonds, and the structure of the monomers is almost maintained within the polymer. The arrangement of the monomers in the copolymer is not necessarily specified to be any one of random copolymers, alternating copolymers, and block copolymers, but random copolymers may be mainly used.
[0037] The acrylic polymer, as a coating layer that prevents polytetrafluoroethylene from agglomerating, has a certain level of durability without agglomerating with other particles, and has the functionality of stably maintaining polytetrafluoroethylene inside the coating layer until polytetrafluoroethylene is fibrous due to heating or pressure. In addition, the acrylic polymer may have the functionality of reinforcing the binding force between components in the dry electrode. The acrylic polymer may have certain levels of physical properties to have the above functionality.
[0038] According to one embodiment of the present invention, the acrylic polymer has a glass transition temperature of 60°C to 150°C. The glass transition temperature is measured according to a conventional measurement method using a DSC (Differential Scanning Calorimeter) device (e.g., manufacturer: TA, product name: Q20). Specifically, the glass transition temperature of the acrylic polymer is 60°C to 150°C, 65°C to 140°C, 70°C to 130°C, or 75°C to 120°C. An acrylic polymer having a glass transition temperature within the above range may have better functionality.
[0039] The weight average molecular weight of the acrylic polymer may also affect the functionality. According to one embodiment of the present invention, the acrylic polymer has a weight average molecular weight of 10,000 g / mol to 600,000 g / mol. Here, the weight average molecular weight is a value converted to a standard polymethyl methacrylate measured by a GPC (Gel Permeation Chromatograph) device (e.g., manufacturer: Waters, product name: Alliance 2695). Specifically, the weight average molecular weight of the acrylic polymer is 10,000 g / mol to 600,000 g / mol, 10,000 g / mol to 300,000 g / mol, or 100,000 g / mol to 200,000 g / mol. An acrylic polymer having a weight average molecular weight within the above range may have better functionality.
[0040] The acrylic polymer can adjust physical properties that affect functionality by adjusting the monomer components constituting the polymer. The methyl methacrylate can be included in the acrylic polymer in the largest amount as a main monomer constituting the acrylic polymer. According to one embodiment of the present invention, the acrylic polymer is a copolymer of monomers containing 40% by weight to 90% by weight of methyl methacrylate based on the total weight of the monomers. Specifically, the content of the methyl methacrylate can be 40% by weight to 90% by weight, or 45% by weight to 90% by weight. The physical properties of the acrylic polymer can be adjusted by combining other types of monomers based on the methyl methacrylate.
[0041] The methyl methacrylate may be combined with other compounds, excluding methyl methacrylate, among the above-mentioned acrylate or methacrylate monomers to produce various kinds of acrylic polymers. According to one embodiment of the present invention, the acrylic polymer is a copolymer of a monomer containing methyl methacrylate and n-butyl acrylate. The n-butyl acrylate contains an n-butyl group having three carbon atoms different from that of methyl methacrylate, and can be easily adjusted to the physical properties required in the present invention even in a small amount compared to other alkyl acrylates. According to one embodiment of the present invention, the n-butyl acrylate is included in an amount of 10 to 60 parts by weight based on 100 parts by weight of methyl methacrylate. When polymerized with methyl methacrylate within the above range, more preferable physical properties can be realized.
[0042] The acrylic polymer may further include a novel functional group so as to have additional functionality such as reinforcing the binding force between components in the dry electrode even after the composite particles are broken by heating or pressure to release the internal polytetrafluoroethylene. Such a functional group may be introduced into the acrylic polymer from a monomer other than alkyl acrylate or alkyl methacrylate, and the functional group may be a carboxylic acid. According to one embodiment of the present invention, the monomer constituting the acrylic polymer further includes acrylic acid or methacrylic acid. According to one embodiment of the present invention, the acrylic acid or methacrylic acid is included in an amount of 40 wt% or less based on the total weight of the monomers. Specifically, the content of the acrylic acid or methacrylic acid may be 40 wt% or less, 30 wt% or less. The acrylic acid or methacrylic acid is not an essential component but an optional component in that it is introduced to impart the above-mentioned additional functionality, and therefore the lower limit of the content may include 0 wt%. However, when the acrylic acid or methacrylic acid is included to secure additional functionality, the acrylic acid or methacrylic acid may be included in a very small amount of 0.1 wt % or more up to the upper limit range described above, and may be included in the acrylic polymer in an amount of, for example, 0.1 wt % to 40 wt %, 5 wt % to 35 wt %, or 10 wt % to 30 wt %. The acrylic acid or methacrylic acid can increase the binding strength not only with polytetrafluoroethylene but also with the electrode active material or conductive material constituting the electrode due to the carboxylic acid protruding from the coating layer.
[0043] The acrylic polymer does not have the property of being easily fibrous like polytetrafluoroethylene, and therefore cannot replace polytetrafluoroethylene as a binder. Therefore, the acrylic polymer is not required in a large amount as long as the above-mentioned functionality can be ensured. According to one embodiment of the present invention, the acrylic polymer is coated on polytetrafluoroethylene in an amount of 5% by weight to 40% by weight based on the total weight of the composite particles. The content of the acrylic polymer may be 5% by weight to 40% by weight, 10% by weight to 30% by weight, or 10% by weight to 20% by weight. Within the above range, a sufficient amount of polytetrafluoroethylene can be included while fully achieving the purpose of introducing the acrylic polymer.
[0044] In the manufacture of electrodes for lithium secondary batteries, a wet method is generally used in which a mixture containing an electrode active material is added to a solvent such as water or an organic solvent and coated on an electrode current collector in the form of a slurry, taking into consideration the processability of the mixture. However, it is not easy to increase the thickness of the electrode due to problems such as the migration of the binder during drying and low adhesion between the electrode current collector and the electrode active material. In order to solve these problems, research has been continued into dry methods that do not use a solvent when manufacturing electrodes, and polytetrafluoroethylene is used as a binder as one means for solving the problem of the decrease in the binding strength of the electrode active material, conductive material, and binder during the dry method. The present invention relates to a polytetrafluoroethylene binder that has been modified with an acrylic polymer to enhance its value, and specifically relates to a dry method for manufacturing electrodes for lithium secondary batteries.
[0045] According to the dry method, the electrode for a lithium secondary battery is manufactured by mixing and dispersing an electrode active material, a conductive material, and a binder, and then applying pressure. As the binder, a composite particle binder according to an embodiment of the present invention is utilized. The electrode can be composed of an active layer and a current collector. The active layer means a layer containing an electrode active material, a conductive material, and a binder. The current collector not only supports the active layer but also plays a role of supplying electrons to the active layer, but there may be cases where the current collector is not necessarily included in the configuration by the active layer. Since the active layer contains an electrode active material, it has activity in the electrochemical reaction within the electrode. In terms of containing the electrode active material, and in terms of being formed by mixing the electrode active material layer, the electrode active material, the conductive material, and the binder, it can be represented as a mixed layer. Also, in the case of all-solid-state batteries where recent research is actively underway, a solid electrolyte can be additionally included.
[0046] The electrode active material can become a positive electrode active material when applied to the positive electrode and can become a negative electrode active material when applied to the negative electrode. The positive electrode active material or the negative electrode active material is not particularly limited as long as it is generally used in the art.
[0047] According to an embodiment of the present invention, the positive electrode active material is a lithium transition metal oxide. In the lithium transition metal oxide, the transition metal is Li 1+x M y O 2+Z (0 ≦ x ≦ 5, 0 < y ≦ 2, 0 ≦ z ≦ 2) has a form, where M is selected from the group consisting of Ni, Co, Mn, Fe, P, Al, Mg, Ca, Zr, Zn, Ti, Ru, Nb, W, B, Si, Na, K, Mo, V, and combinations thereof, and is not particularly limited within the above range. More specifically, the lithium transition metal oxide is LiCoO 2 , LiNiO 2 , LiMnO 2 , Li 2 MnO 3 , LiMn 2 O 4 , Li(Ni a Co b Mn c )O 2(0 < a < 1, 0 < b < 1, 0 < c < 1, a + b + c = 1), LiNi 1-y Co y O 2 (0 < y < 1), LiCo 1-y Mn y O 2 、LiNi 1-y Mn y O 2 (0 < y < 1), Li(Ni a Co b Mn c )O 4 (0 < a < 2, 0 < b < 2, 0 < c < 2, a + b + c = 2), LiMn 2-z Ni z O 4 (0 < z < 2), LiMn 2-z Co z O 4 is selected from (0 < z < 2) and combinations thereof.
[0048] According to one embodiment of the present invention, the negative electrode active material is a compound capable of reversible intercalation and deintercalation of lithium. Specific examples include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, or Al alloys; SiO β (0 < β < 2), SnO 2Examples of the negative electrode active material include metal oxides capable of doping and dedoping lithium, such as vanadium oxide and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites and Sn-C composites, and any one or a mixture of two or more of these may be used. In addition, a thin film of metallic lithium may be used as the negative electrode active material. In addition, both low-crystalline carbon and high-crystalline carbon may be used as the carbon material. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, flaky, spherical or fibrous natural or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, meso-carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes. In addition, the composition may further include metal nanoparticles having lithophilic properties. The metal nanoparticles may be one or more selected from silver, gold, platinum, palladium, silicon, aluminum, bismuth, tin, indium, zinc, etc., and may be silver.
[0049] According to one embodiment of the present invention, the electrode active material is a lithium transition metal oxide having an average particle diameter of 5 μm to 30 μm. Specifically, the average particle diameter may be 5 μm or more, 6 μm or more, 7 μm or more, 8 μm or more, 9 μm or more, 10 μm or more, 30 μm or less, 28 μm or less, 26 μm or less, 24 μm or less, 22 μm or less, 20 μm or less, or 5 μm to 30 μm, 7 μm to 24 μm, or 10 μm to 20 μm.
[0050] The conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it does not cause chemical changes in the battery and has electronic conductivity.Specific examples include graphite such as natural graphite and artificial graphite; carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, summer black, single-layer or multi-layer carbon nanotubes, carbon fibers, carbon nanofibers, graphene, activated carbon, activated carbon fibers, and other carbon-based materials; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in mixture.
[0051] The conductive material may be a carbonaceous material or a metal material, and the metal material may include the above-mentioned metal powder, metal fiber, conductive metal oxide, etc. The conductive material may be spherical or linear particles. When the conductive material is a spherical particle, the average diameter of the particle may be 1 nm to 100 nm, specifically 5 nm to 70 nm, more specifically 10 nm to 40 nm. When the conductive material is a linear particle, the length of the linear particle may be 1 μm to 10 μm, specifically 2 μm to 9 μm, more specifically 3 μm to 8 μm, and the diameter of the vertical cross section may be 10 nm to 500 nm, specifically 50 nm to 350 nm, more specifically 100 nm to 200 nm.
[0052] The binder serves to improve the adhesion between the electrode active material particles and the adhesive strength between the electrode active material and the electrode current collector. In one embodiment of the present invention, the composite particles described above are used as a binder, and the composite particles, which do not easily aggregate, are mixed with the electrode active material and the conductive material and uniformly dispersed. Then, the composite particles are fiberized and pressed by equipment such as a roll, during which the acrylic polymer coating layer is broken, and the polytetrafluoroethylene inside is released, and fiberization proceeds due to the applied shear force. Due to the excellent dispersibility of the composite particles in the active layer, the present invention can maximize the functionality of the binder. The acrylic polymer coating layer may be broken by heating, and when the composite particles are mixed while being heated, fiberization of the polytetrafluoroethylene may proceed simultaneously with mixing.
[0053] According to one embodiment of the present invention, the binder is contained in the active layer in an amount of 0.1 wt % to 10 wt %, specifically 0.5 wt % to 5 wt %, more specifically 1 wt % to 3 wt %, based on the total weight of the electrode active material, the conductive material and the binder. The present invention is significant in that it can increase the binding strength of the entire active layer even with a small amount of binder.
[0054] The electrode according to an embodiment of the present invention does not necessarily require an electrode current collector in that the shape can be fixed by fiberization of the binder, but the electrode current collector can be used in that it can be a uniform electron transfer path in the relationship between the conductor and the active layer of the battery. The electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the electrode current collector can usually have a thickness of 3 to 500 μm, and fine irregularities can be formed on the surface of the electrode current collector to increase the adhesive force of the electrode active material. For example, it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc. In addition, the electrode current collector can be a primer coated foil, and the electrode current collector material can include a surface layer coated with a conductive carbon material and a binder.
[0055] The above-mentioned electrode can be applied to a lithium secondary battery, which is generally manufactured by inserting a separator between a positive electrode and a negative electrode and then injecting an electrolyte, but can be modified into various forms, such as by mixing a solid electrolyte, if necessary.
[0056] The separator separates the negative electrode and the positive electrode and provides a passage for lithium ions to move. Any separator that is generally used in lithium secondary batteries may be used without any particular limitation. In particular, a separator that has low resistance to electrolyte ion movement and excellent electrolyte humidification ability is preferred. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, a coated separator containing a ceramic component or a polymeric material to ensure heat resistance or mechanical strength may be used, and may be selectively used in a single layer or multilayer structure.
[0057] The electrolyte may be a liquid electrolyte, a solid electrolyte, or the like that can be used in manufacturing a lithium secondary battery, but is not limited thereto.
[0058] Typically, the liquid electrolyte can include an organic solvent and a lithium salt.
[0059] The organic solvent can be used without any particular limitation as long as it can act as a medium through which ions involved in the electrochemical reaction of the battery can move.Specific examples of the organic solvent include ester solvents such as methyl acetate, ethyl acetate, γ-butyrolactone, and ε-caprolactone; ether solvents such as dibutyl ether and tetrahydrofuran; ketone solvents such as cyclohexanone; aromatic hydrocarbon solvents such as benzene and fluorobenzene; dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), propylene carbonate, Carbonate-based solvents such as PC; alcohol-based solvents such as ethyl alcohol and isopropyl alcohol; nitriles such as R-CN (R is a C2-C20 straight-chain, branched or ring-structured hydrocarbon group, which may contain a double-bonded aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant, which can enhance the charge / discharge performance of a battery, and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred. In this case, the cyclic carbonate and the chain carbonate are mixed in a volume ratio of about 1:1 to about 1:9 to exhibit excellent performance of the electrolyte.
[0060] The lithium salt can be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the lithium salt is LiPF 6 , LiClO 4 , LiAsF 6 , LiBF 4 , LiSbF 6 , LiAl0 4 , LiAlCl 4 , LiCF 3 SO 3 , LiC 4 F 9 SO 3 , LiN(C 2 F 5 SO 3 ) 2 , LiN(C 2 F 5 SO 2 ) 2 , LiN(CF 3 SO 2 ) 2 , LiCl, LiI, or LiB(C 2 O 4 ) 2 The lithium salt may be used at a concentration within the range of 0.1 to 2.0 M. When the lithium salt concentration is within the above range, the electrolyte has appropriate conductivity and viscosity, and therefore can exhibit excellent electrolyte performance and can effectively move lithium ions.
[0061] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in battery capacity, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1 to 5 wt % based on the total weight of the electrolyte.
[0062] In the electrode according to an embodiment of the present invention, a solid electrolyte may also be preferably used since it is manufactured by a dry method. The solid electrolyte may include an ion-conductive solid electrolyte material. The ion-conductive solid electrolyte material may include at least one of a polymer solid electrolyte and an inorganic solid electrolyte. The polymer solid electrolyte may include a polymer resin and a lithium salt, and may be a solid polymer electrolyte having a form of a mixture of a solvated lithium salt and a polymer resin, or a polymer gel electrolyte in which an organic electrolyte solution containing an organic solvent and a lithium salt is contained in a polymer resin. Hereinafter, the ion-conductive solid electrolyte material will be described in detail to the extent that it does not overlap with the description of the liquid electrolyte.
[0063] The solid polymer electrolyte may include, but is not limited to, one or more materials selected from the group consisting of polyether-based polymers, polycarbonate-based polymers, acrylate-based polymers, polysiloxane-based polymers, phosphazene-based polymers, polyethylene derivatives, alkylene oxide derivatives, phosphate ester polymers, polyagitation lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, and polymers containing ionic dissociation groups. The solid polymer electrolyte may include, but is not limited to, one or more materials selected from the group consisting of branched copolymers in which amorphous polymers such as PMMA, polycarbonate, polysiloxane (pdms), and / or phosphazene are copolymerized with a comonomer on a polyethylene oxide (PEO) main chain, comb-like polymers, and crosslinked polymer resins.
[0064] The polymer gel electrolyte includes an organic electrolyte solution containing a lithium salt and a polymer resin, and the organic electrolyte solution may include 60 to 400 parts by weight based on the weight of the polymer resin. The polymer resin applied to the gel electrolyte may be, for example, one or more materials selected from the group consisting of PVC (Polyvinyl chloride), PMMA (Poly(methyl methacrylate)), polyacrylonitrile (PAN), polyvinylidene fluoride (PVdF), and polyvinylidene fluoride-hexafluoropropylene (PVdF-HFP), but is not necessarily limited thereto.
[0065] The inorganic solid electrolyte may be a sulfide-based solid electrolyte, a halide-based solid electrolyte, an oxide-based solid electrolyte, or one containing at least one of these.
[0066] The sulfide-based solid electrolyte is an electrolyte component containing sulfur atoms, and is not particularly limited to a specific component, and may include one or more of a crystalline solid electrolyte, a non-crystalline solid electrolyte (a glassy solid electrolyte), and a glass ceramic solid electrolyte. Specific examples of the sulfide-based solid electrolyte include an LPS-type sulfide containing sulfur and phosphorus, a Li 4-x Ge 1-x P x S 4 (x is 0.1 to 2, specifically, x is 3 / 4, 2 / 3), Li 10±1 MP 2 X 12 (M=Ge, Si, Sn, Al, X=S, Se), Li 3.833 Sn 0.833 As 0.166 S 4 , Li 4 SnS 4 , Li 3.25 Ge 0.25 P 0.75 S 4 , Li 2 SP 2 S 5 , B 2 S 3 -Li 2 S, xLi 2 S-(100-x)P 2 S 5 (x is 70~80), Li 2 S-SiS 2 -Li 3 N, Li 2 SP 2 S 5 - LiI, Li 2 S-SiS 2 - LiI, Li 2 S.B. 2 S 3 -LiI, but is not limited to these.
[0067] The halide-based solid electrolyte is Li 3 Y.C.L. 6 and Li 3 YBr 6 The present invention may include at least one of the above, but is not limited to these.
[0068] The oxide-based solid electrolyte is, for example, Li 3x La 2 / 3-x TiO 3 The LLT series with perovskite structure, such as Li 14 Zn(GeO 4 ) 4 Like LISICON, Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 LATP systems such as (Li 1+x Ge 2-x Al x (PO 4 ) 3 ), phosphate-based such as LiPON, etc. can be appropriately selected and used, but are not necessarily limited to these.
[0069] As described above, the lithium secondary battery including the electrode according to the present invention stably exhibits excellent discharge capacity, output characteristics, and capacity retention rate, and is therefore useful in portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs), etc.
[0070] According to another aspect of the present invention, there is provided a battery module including the lithium secondary battery as a unit cell, and a battery pack including the same. The battery module or battery pack may be used in, but is not limited to, a power tool; an electric vehicle, including an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); an electric two-wheeled vehicle, including an electric bicycle (E-bike) and an electric scooter (E-scooter); an electric golf cart; an Urban Air Mobility (UAM); or a power storage system.
[0071] Preferred examples are shown below to aid in understanding the present invention. The following examples are provided to facilitate understanding of the present invention, and the present invention is not limited thereto.
[0072] Manufacturing example (manufacturing composite particles) Production Example 1: Uses an acrylic polymer polymerized with 100% by weight of methyl methacrylate monomer. An aqueous polytetrafluoroethylene dispersion (DISP30 from Chemours) was prepared, having an average particle diameter of 0.22 μm, a solid content concentration of 60%, and a standard specific gravity (SSG) after sintering of 2.22.
[0073] Next, 1020.0g of polytetrafluoroethylene aqueous dispersion and 1843.4g of distilled water were placed in a 4L reactor, and the temperature was raised to 75°C while stirring at a speed of 350 RPM and bubbling with nitrogen. After reaching the polymerization temperature of 75°C, the nitrogen bubbling was stopped, and 15 minutes later, 153g of methyl methacrylate (MMA) was added dropwise to the reactor over 15 minutes. 15 minutes after the monomer addition, 10g of distilled water and 0.77g of ammonium persulfate aqueous solution were added dropwise to the reactor over about 10 minutes. After the polymerization reaction was carried out for 4 hours after the end of the addition of ammonium persulfate, it was cooled to 30°C to obtain a white emulsion.
[0074] The white emulsion after polymerization was diluted 1,000 times and analyzed for size using NICOMP 380 (Entegris, dynamic light scattering) and listed in Table 1 below. To analyze the particle structure, a drop of the emulsion diluted with water was placed on a transmission electron microscope (TEM) grid and dried at room temperature. The structure of the dried sample was analyzed using TEM / EDS (FEI's TECNAI TF20) at an accelerating voltage of 200kV and is shown in Figure 1 below.
[0075] The emulsion was then freeze-dried for 72 hours under conditions of -60°C and 10 mTorr to obtain a white powder.
[0076] In the above-mentioned method, an acrylic polymer (weight average molecular weight (M w ): 543,000g / mol, glass transition temperature (T g ):120.2℃) was coated onto polytetrafluoroethylene, which is the material constituting the interior of the composite particles, to produce composite particles with an average particle diameter of 0.3 μm. In the produced composite particles, the weight ratio of polytetrafluoroethylene to acrylic polymer was 80:20.
[0077] Preparation Example 2: An acrylic polymer polymerized with 90% by weight of methyl methacrylate and 10% by weight of n-butyl acrylate monomer is used. The same method as in Preparation Example 1 was used to prepare the copolymer, except that a mixed monomer of 137.7 g of methyl methacrylate and 15.3 g of n-butyl acrylate and 0.21 g of a chain transfer agent, n-octyl mercaptan, were used.
[0078] In the above-mentioned method, the material constituting the outer part of the composite particle is an acrylic polymer (weight average molecular weight (M w ): 182,000g / mol, glass transition temperature (T g ): 101.4°C) was coated on the same polytetrafluoroethylene as in Production Example 1, which is the material constituting the interior of the composite particles, to produce composite particles (average particle diameter: 0.3 μm, weight ratio of polytetrafluoroethylene to acrylic polymer: 80:20).
[0079] Preparation Example 3: An acrylic polymer polymerized with 80% by weight of methyl methacrylate and 20% by weight of n-butyl acrylate monomers is used. The same method as in Preparation Example 1 was used to prepare the copolymer, except that a mixed monomer of 122.4 g of methyl methacrylate and 30.6 g of n-butyl acrylate and 0.21 g of a chain transfer agent, n-octyl mercaptan, were used.
[0080] In the above-mentioned method, an acrylic polymer (weight average molecular weight (M w ): 193,000g / mol, glass transition temperature (T g (average particle diameter: 0.3 μm, weight ratio of polytetrafluoroethylene to acrylic polymer: 80:20) was produced by coating the same polytetrafluoroethylene as in Production Example 1, which is the material constituting the interior of the composite particles, with the above-mentioned mixture.
[0081] Preparation Example 4: An acrylic polymer polymerized with 70% by weight of methyl methacrylate and 30% by weight of n-butyl acrylate monomers is used. The same method as in Preparation Example 1 was used to prepare the copolymer, except that a mixed monomer of 107.1 g of methyl methacrylate and 45.9 g of n-butyl acrylate and 0.37 g of a chain transfer agent, n-octyl mercaptan, were used.
[0082] In the above-mentioned method, an acrylic polymer (weight average molecular weight (M)) polymerized with 70% by weight of methyl methacrylate and 30% by weight of n-butyl acrylate monomer, which is the material constituting the outer part of the composite particle, is used. w ): 128,000g / mol, glass transition temperature (T g (average particle diameter: 0.3 μm, weight ratio of polytetrafluoroethylene to acrylic polymer: 80:20) was produced by coating the same polytetrafluoroethylene as in Production Example 1, which is the material constituting the interior of the composite particles, with the above-mentioned mixture.
[0083] Preparation Example 5: An acrylic polymer polymerized with 50% by weight of methyl methacrylate and 50% by weight of methacrylic acid monomer is used. The same method as in Preparation Example 1 was used to prepare the copolymer, except that a mixed monomer of 76.5 g of methyl methacrylate and 76.5 g of methacrylic acid and 0.21 g of a chain transfer agent, n-octyl mercaptan, were used.
[0084] In the above-mentioned method, an acrylic polymer (weight average molecular weight (M)) polymerized with 50% by weight of methyl methacrylate and 50% by weight of methacrylic acid monomer, which is the material constituting the outer part of the composite particle, is used. w ): 188,000g / mol, glass transition temperature (T g ): 140.4°C) was coated on the same polytetrafluoroethylene as in Production Example 1, which is the material constituting the interior of the composite particles, to produce composite particles (average particle diameter: 0.3 μm, weight ratio of polytetrafluoroethylene to acrylic polymer: 80:20).
[0085] Preparation Example 6: An acrylic polymer polymerized with 70% by weight of methyl methacrylate and 30% by weight of methacrylic acid monomer is used. The same method as in Preparation Example 1 was used to prepare the copolymer, except that a mixed monomer of 107.1 g of methyl methacrylate and 45.9 g of methacrylic acid and 0.21 g of a chain transfer agent, n-octyl mercaptan, were used.
[0086] In the above-mentioned method, the material constituting the outer part of the composite particle is an acrylic polymer (weight average molecular weight (M w ): 203,000g / mol, glass transition temperature (T g ): 131.2°C) was coated onto the same polytetrafluoroethylene as in Production Example 1, which is the material constituting the interior of the composite particles, to produce composite particles (average particle diameter: 0.3 μm, weight ratio of polytetrafluoroethylene to acrylic polymer: 80:20).
[0087] Preparation Example 7: An acrylic polymer polymerized with 90% by weight of methyl methacrylate and 10% by weight of methacrylic acid monomer is used. The same method as in Preparation Example 1 was used to prepare the copolymer, except that a mixed monomer of 137.1 g of methyl methacrylate and 15.3 g of methacrylic acid and 0.21 g of a chain transfer agent, n-octyl mercaptan, were used.
[0088] In the above-mentioned method, the material constituting the outer part of the composite particle is an acrylic polymer (weight average molecular weight (M w ): 211,000g / mol, glass transition temperature (T g ): 122.4°C) was coated on the same polytetrafluoroethylene as in Production Example 1, which is the material constituting the interior of the composite particles, to produce composite particles (average particle diameter: 0.3 μm, weight ratio of polytetrafluoroethylene to acrylic polymer: 80:20).
[0089] Preparation Example 8: An acrylic polymer polymerized with 45% by weight of methyl methacrylate, 25% by weight of n-butyl acrylate, and 30% by weight of methacrylic acid monomer is used. The same method as in Preparation Example 1 was used to prepare the copolymer, except that a mixed monomer of 68.85 g of methyl methacrylate, 38.25 g of n-butyl acrylate, and 45.9 g of methacrylic acid and 0.28 g of a chain transfer agent, n-octyl mercaptan, were used.
[0090] In the above-mentioned method, the material constituting the outer part of the composite particle is an acrylic polymer (weight average molecular weight (M w ): 168,000g / mol, glass transition temperature (T g The same polytetrafluoroethylene as in Production Example 1, which is the material constituting the interior of the composite particles, was coated with a polytetrafluoroethylene / acrylic polymer solution (average particle diameter: 0.3 μm, weight ratio of polytetrafluoroethylene to acrylic polymer: 80:20) to produce composite particles (average particle diameter: 0.3 μm, weight ratio of polytetrafluoroethylene to acrylic polymer: 80:20).
[0091] Production Example 9: Production of composite particles having a weight ratio of polytetrafluoroethylene and acrylic polymer of 90:10 The same method as in Preparation Example 1 was used to prepare the polymer, except that 1147.5 g of polytetrafluoroethylene aqueous dispersion and 1807.7 g of distilled water were used, and a mixed monomer of 61.2 g of methyl methacrylate and 15.3 g of n-butyl acrylate, 0.38 g of ammonium persulfate as an initiator, and 0.11 g of n-octyl mercaptan as a chain transfer agent were used.
[0092] In the above-mentioned method, an acrylic polymer (weight average molecular weight (M w ): 185,000g / mol, glass transition temperature (T g (80.1°C) was coated onto the same polytetrafluoroethylene as in Production Example 1, which was the material constituting the interior of the composite particles, to produce composite particles (average particle diameter: 0.3 µm, weight ratio of polytetrafluoroethylene to acrylic polymer: 90:10).
[0093] Production Example 10: Production of composite particles having a weight ratio of polytetrafluoroethylene and acrylic polymer of 70:30 The same method as in Preparation Example 1 was used to prepare the polymer, except that 892.5 g of polytetrafluoroethylene aqueous dispersion and 1879.1 g of distilled water were used, and mixed monomers of 183.6 g of methyl methacrylate and 45.9 g of n-butyl acrylate, 1.15 g of ammonium persulfate as initiator and 0.32 g of n-octyl mercaptan as chain transfer agent were used.
[0094] In the above-mentioned method, an acrylic polymer (weight average molecular weight (M w ): 183,000g / mol, glass transition temperature (T g The same polytetrafluoroethylene as in Production Example 1, which is the material constituting the interior of the composite particles, was coated with a polytetrafluoroethylene / acrylic polymer solution (average particle diameter: 0.3 μm, weight ratio of polytetrafluoroethylene to acrylic polymer: 70:30) to produce composite particles (average particle diameter: 0.3 μm, weight ratio of polytetrafluoroethylene to acrylic polymer: 70:30).
[0095] Production Example 11: Production of composite particles having a weight ratio of polytetrafluoroethylene and acrylic polymer of 50:50 The same method as in Preparation Example 1 was used, except that 637.5 g of polytetrafluoroethylene aqueous dispersion and 1950.5 g of distilled water were used, and mixed monomers of 306.0 g of methyl methacrylate and 76.5 g of n-butyl acrylate, 1.91 g of ammonium persulfate as initiator, and 0.54 g of n-octyl mercaptan as chain transfer agent were used.
[0096] In the above-mentioned method, an acrylic polymer (weight average molecular weight (M w ): 180,000g / mol, glass transition temperature (T g (80.5°C) was coated onto the same polytetrafluoroethylene as in Production Example 1, which was the material constituting the interior of the composite particles, to produce composite particles (average particle diameter: 0.3 µm, weight ratio of polytetrafluoroethylene to acrylic polymer: 50:50).
[0097] Production Example 12: Production of composite particles having a weight ratio of polytetrafluoroethylene (standard specific gravity (SSG): 2.31) and acrylic polymer of 80:20 It was produced in the same manner as in Production Example 1, except that an aqueous polytetrafluoroethylene dispersion (product of Chemours) having an average particle diameter of 0.22 μm, a solid content concentration of 60%, and a standard specific gravity (SSG) after sintering of 2.31 was used.
[0098] In the above-mentioned method, an acrylic polymer (weight average molecular weight (M w ): 505,000g / mol, glass transition temperature (T g):121.0℃) was coated onto polytetrafluoroethylene, which is the material constituting the interior of the composite particles, to produce composite particles with an average particle diameter of 0.3 μm. In the produced composite particles, the weight ratio of polytetrafluoroethylene to the acrylic polymer was 80:20.
[0099] Example (electrode using composite particles) Example 1: Use of composite particles of Production Example 1 A positive electrode active material NCM particle powder (product: GL80, manufacturer: LG Chem) with an average particle size of 10 μm was prepared at 95.5 wt%, a conductive material (product: Li-250, manufacturer: Denka) at 1.5 wt%, and a binder at 3.0 wt% of the composite particles of Preparation Example 1. The prepared electrode active material, conductive material, and binder were mixed in a Lab Blender (manufacturer: Waring) and mixed at 10,000 RPM for 30 seconds 10 times to prepare a mixture for a dry electrode. The mixture was subjected to high shear mixing at 100 RPM at 100 °C for 5 minutes using a Twin Screw Kneader (manufacturer: Irie Shokai) while applying a shear force at 100 RPM, and fiberization was carried out under heating conditions. Next, the dough-like secondary mixture was prepared at 100° C. using a Two Roll Mill (manufacturer: Inoue) to prepare a free-standing film having a thickness of 200 μm.
[0100] Example 2: Use of composite particles of Production Example 2 An electrode was produced in the same manner as in Example 1, except that the composite particles of Production Example 2 were used as the binder.
[0101] Example 3: Use of composite particles of Production Example 3 An electrode was produced in the same manner as in Example 1, except that the composite particles of Production Example 3 were used as the binder.
[0102] Example 4: Use of composite particles of Production Example 4 An electrode was produced in the same manner as in Example 1, except that the composite particles of Production Example 4 were used as the binder.
[0103] Example 5: Use of composite particles of Production Example 5 An electrode was produced in the same manner as in Example 1, except that the composite particles of Production Example 5 were used as the binder.
[0104] Example 6: Use of composite particles of Production Example 6 An electrode was produced in the same manner as in Example 1, except that the composite particles of Production Example 6 were used as the binder.
[0105] Example 7: Use of composite particles of Production Example 7 An electrode was produced in the same manner as in Example 1, except that the composite particles of Production Example 7 were used as the binder.
[0106] Example 8: Use of composite particles of Production Example 8 An electrode was produced in the same manner as in Example 1, except that the composite particles of Preparation Example 8 were used as the binder.
[0107] Example 9: Use of the composite particles of Preparation Example 3 (binder content: 1.5% by weight) An electrode was manufactured in the same manner as in Example 1, except that the electrode active material was adjusted to 95.5 wt %, the conductive material was adjusted to 1.5 wt %, and the binder was adjusted to 1.5 wt %.
[0108] Example 10: Use of composite particles of Production Example 9 An electrode was produced in the same manner as in Example 1, except that the composite particles of Production Example 9 were used as the binder.
[0109] Example 11: Use of composite particles of Production Example 10 An electrode was produced in the same manner as in Example 1, except that the composite particles of Preparation Example 10 were used as the binder.
[0110] Comparative Example 1: Composite particles of Production Example 11 are used An electrode was produced in the same manner as in Example 1, except that the composite particles of Production Example 11 were used as the binder.
[0111] Comparative Example 2: Use of polytetrafluoroethylene particles An electrode was produced in the same manner as in Example 1, except that the composite particles of Preparation Example 12 were used as the binder.
[0112] Comparative Example 3: Use of polytetrafluoroethylene particles (binder content: 1.5% by weight) An electrode was manufactured in the same manner as in Example 33, except that the electrode active material was adjusted to 97.0 wt %, the conductive material was adjusted to 1.5 wt %, and the binder was adjusted to 1.5 wt %.
[0113] Comparative Example 4: Use of polytetrafluoroethylene particles (mixed at room temperature) An electrode was manufactured in the same manner as in Example 3, except that the prepared electrode active material, conductive material, and binder were mixed at room temperature.
[0114] Experimental example (electrode evaluation) Experimental Example 1: Evaluation of thickness deviation and tensile strength of free-standing film-type electrodes The free-standing film-type electrodes prepared according to Examples 1 to 10 and Comparative Examples 1 to 5 were sampled to have a width of 20 mm, a length of 20 mm, and a thickness of 200 μm, and the thickness deviation and tensile strength of the samples were measured. The thickness deviation was measured using an electrode thickness measuring device (product: Millimar, manufacturer: Mahr), and the tensile strength was measured using a UTM device (manufacturer: LLOYD). The tensile strength was measured by measuring the maximum force applied until the film did not break under conditions of an angle of 180 degrees and a speed of 50 mm / min. The results for the thickness deviation and tensile strength are shown in Table 1 below.
[0115] [Table 1]
[0116] According to Table 1, the electrodes according to Examples 1 to 11 have a small thickness deviation and a tensile strength of 2,400 gf / cm 2The physical properties were confirmed to be at a good level. On the other hand, the electrodes according to Comparative Examples 1 to 4 had a tensile strength of 2,200 gf / cm 2 The following physical properties were confirmed to be at an insufficient level: In addition, it was shown that the electrodes according to Comparative Examples 2 to 4 used polytetrafluoroethylene, which has a high standard specific gravity (SSG) of 2.31, had a significantly large thickness deviation.
[0117] Experimental example 2: Performance evaluation of batteries using electrodes A free-standing film having a thickness of 200 μm was prepared according to Examples 1 to 10 and Comparative Examples 1 to 5, and the free-standing film was placed on one side of a current collector having a thickness of 20 μm, Primer Coated Aluminum Foil (manufacturer: Dongwon Systems), and bonded using a lamination roll maintained at 120° C. to prepare a positive electrode. Lithium metal was used as the counter electrode, and 1M LiPF 6 A half cell was manufactured using an electrolyte solution containing the above.
[0118] The prepared coin-type half cell was charged and discharged 100 times at 25° C. in the voltage range of 3 to 4.3 V and at a current condition of 0.33 C-rate, and then the discharge capacity retention rate of 100 times relative to the discharge capacity of one time was calculated. The results are shown in Table 2 below.
[0119] [Table 2]
[0120] According to Table 2, the electrodes according to Examples 1 to 11 have a 100-cycle discharge capacity retention rate of 95% or more, which is an improved effect compared to the electrodes according to Comparative Examples 1 to 4, whose capacity retention rates are less than 95%.
[0121] Any simple modifications or variations of the present invention belong to the scope of the present invention, and the specific scope of protection of the present invention will be made clear by the appended claims.
Claims
1. A binder for lithium secondary batteries comprising composite particles of polytetrafluoroethylene structure coated with an acrylic polymer.
2. The binder for a lithium secondary battery according to claim 1, wherein the composite particles have an average diameter of 0.01 μm to 2 μm.
3. The acrylic polymer is a polymer of a monomer including an alkyl acrylate, an alkyl methacrylate, or a combination thereof; 2. The binder for a lithium secondary battery according to claim 1, wherein the alkyl has 1 to 10 carbon atoms.
4. 2. The binder for a lithium secondary battery according to claim 1, wherein the acrylic polymer has a glass transition temperature of 60°C to 150°C.
5. 2. The binder for a lithium secondary battery according to claim 1, wherein the acrylic polymer has a weight average molecular weight of 10,000 g / mol to 300,000 g / mol.
6. 4. The binder for a lithium secondary battery according to claim 3, wherein the acrylic polymer is a copolymer of monomers containing 40% by weight to 90% by weight of methyl methacrylate based on the total weight of the monomers.
7. 7. The binder for a lithium secondary battery according to claim 6, wherein the acrylic polymer is a copolymer of monomers including methyl methacrylate and n-butyl acrylate.
8. 2. The binder for a lithium secondary battery according to claim 1, wherein the acrylic polymer is coated on the polytetrafluoroethylene in an amount of 5 to 40% by weight based on the total weight of the composite particles.
9. 8. The binder for a lithium secondary battery according to claim 7, wherein the n-butyl acrylate is contained in an amount of 10 to 60 parts by weight based on 100 parts by weight of methyl methacrylate.
10. The binder for a lithium secondary battery according to claim 6, wherein the monomer further comprises acrylic acid or methacrylic acid.
11. The binder for a lithium secondary battery according to claim 10, wherein the acrylic acid or methacrylic acid is present in an amount of 0.1% by weight to 40% by weight based on the total weight of the monomers.
12. The binder for a lithium secondary battery according to claim 1, wherein the polytetrafluoroethylene has a standard specific gravity (SSG) of 2.3 or less.
13. 13. An electrode for a lithium secondary battery, produced by mixing the binder according to any one of claims 1 to 12, an electrode active material and a conductive material, and then applying pressure.
14. 14. The electrode for a lithium secondary battery according to claim 13, wherein the binder is contained in the electrode in an amount of 0.1 to 10 wt % based on the total weight of the binder, the electrode active material, and the conductive material.
Citation Information
Patent Citations
Low-temperature-forming self-lubricating material and preparation method thereof
CN110128597A
Preparation method of polytetrafluoroethylene core-shell type composite particles
CN110818844A
Production of silicone foamed article
JP1997012764A
Nonaqueous electrolyte secondary battery and its manufacture
JP1999260411A
Non-aqueous electrolyte secondary battery
JP1999329439A